Organizational Safety Support Practices and Employee Performance in the Department of Health Services in Makueni County, Kenya: Organizational Safety Support Practices - Ndolo, Jackson (Archives of Business Research, 2020)
Many organizations across the globe have adopted occupational safety practices notably organizational safety support in order to improve the working conditions and eventually promote employee performance. However the relationship between organizational safety support and employee performance, has not been well established especially in Kenyan public sector a situation that informed the current study. This study adopted a descriptive research design and targeted an overall 428 employee population. A stratified proportionate sampling was used to obtain a sample of 207 respondents. Structured questionnaires were the main instruments of data collection. Both descriptive and inferential statistics was used to analyze data aided by SPSS. Study results were presented using tables, charts and graphs. The study realized a 72.2% response rate. Key findings of the study included; the department of health services in the county had embraced various occupational safety practices. Organizational safety support was found to influence 58.8% of the variations in employee performance. Through safety support practices the department had provided a conducive working environment which in turn had translated to high staff productivity. The findings of the study may find use among public sector managers and policy makers. To uphold research ethics, NACOSTI, MKU ERC and the Governor’s Office, Government of Makueni County permission was sought before data was collected.